Amendment effectiveness and seasonal variations in a lead contaminated acidic wetland - Matthew R. Noerpel; Anna M. Wade; Aaron R. Betts; Jennifer Goetz; Robert Ford; Amy Krause; Michael Zeolla; Diana Cutt; Stephanie M. Wilson; Todd P. Luxton (Applied Geochemistry, 2025)

Mobilization of porewater Pb and Zn in response to seasonal wetting and drying within contaminated floodplains - Anna M. Wade; Chris S. Eckley; Matthew Noerpel; Jennifer Goetz; David Leptich; Kim Prestbo; David Van de Riet; Steve Sluka; Richard Wilkin; Todd P. Luxton (Science of The Total Environment, 2025)

Correction: Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)

Prey targeted by lactating Weddell seals (Leptonychotes weddellii) in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Daniel P. Costa; David G. Ainley; Matthew H. Pinkerton; Michelle A. LaRue (Polar Biology, 2024)
Female Weddell seals ( Leptonychotes weddellii ) display a mixed capital-income breeding strategy, losing up to 40% of their body mass between birthing and weaning their pups. How and when they regain energy stores, however, remains to be fully explored. To better understand the foraging by lactating Weddell seals, we fitted time-depth recorders and head-mounted cameras on 26 seals in Erebus Bay, Ross Sea, for ~ 5 days in November and December 2018 and 2019. We aimed to (1) identify prey species and foraging depth and (2) investigate relationships between seal physiology and demographics and probability of foraging. We recorded 2782 dives, 903 of which were > 50 m, maximum depth was 449.3 m and maximum duration was 31.1 min. Pup age likely contributes to the probability of a lactating Weddell seal foraging (Est. = 1.21 (SD = 0.61), z = 1.97, p = 0.0484). Among 846 prey encounters, the most frequent prey items were crustaceans (46.2%) and Antarctic silverfish ( Pleuragramma antarcticum , 19.0%); two encounters were observed with juvenile Antarctic toothfish ( Dissostichus mawsoni , 0.2%). We identified substantial variability in foraging behaviour, individually and between locations, and found that lactating seals target many species and some may specialise on certain prey groups.

First observations of Weddell seals foraging in sponges in Erebus Bay, Antarctica - Rose T. N. Foster-Dyer; Kimberly T. Goetz; Matthew H. Pinkerton; Takashi Iwata; Rachel R. Holser; Sarah A. Michael; Craig Pritchard; Simon Childerhouse; Jay Rotella; Luisa Federwisch; Daniel P. Costa; Michelle A. LaRue (Polar Biology, 2023)
Attaching cameras to marine mammals allows for first-hand observation of underwater behaviours that may otherwise go unseen. While studying the foraging behaviour of 26 lactating Weddell seals ( Leptonychotes weddellii ) in Erebus Bay during the austral spring of 2018 and 2019, we witnessed three adults and one pup investigating the cavities of Rossellidae glass sponges, with one seal visibly chewing when she removed her head from the sponge. To our knowledge, this is the first report of such behaviour. While the prey item was not identifiable, some Trematomus fish (a known Weddell seal prey) use glass sponges for shelter and in which to lay their eggs. Three of the four sponge foraging observations occurred around 13:00 (NZDT). Two of the three sponge foraging adults had higher-than-average reproductive rates, and the greatest number of previous pups of any seal in our study population, each having ten pups in 12 years. This is far higher than the study population average of three previous pups (± 2.6 SD). This novel foraging strategy may have evolved in response to changes in prey availability, and could offer an evolutionary advantage to some individuals that exploit prey resources that others may not. Our observations offer new insight into the foraging behaviours of one of the world’s most studied marine mammals. Further research on the social aspects of Weddell seal behaviour may increase our understanding of the extent and mechanisms of behavioural transfer between conspecifics. Research into the specific foraging behaviour of especially successful or experienced breeders is also warranted.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ontogenetic changes in embryonic and brain gene expression in progeny produced from migratory and resident O ncorhynchus mykiss - Garrett J. McKinney; Matthew C. Hale; Giles Goetz; Michael Gribskov; Frank P. Thrower; Krista M. Nichols (Molecular Ecology, 2015)
Little information has been gathered regarding the ontogenetic changes that contribute to differentiation between resident and migrant individuals, particularly before the onset of gross morphological and physiological changes in migratory individuals. The aim of this study was to evaluate gene expression during early development in Oncorhynchus mykiss populations with different life histories, in a tissue known to integrate environmental cues to regulate complex developmental processes and behaviours. We sampled offspring produced from migrant and resident parents, collecting whole embryos prior to the beginning of first feeding, and brain tissue at three additional time points over the first year of development. RNA sequencing for 32 individuals generated a reference transcriptome of 30 177 genes that passed count thresholds. Differential gene expression between migrant and resident offspring was observed for 1982 genes. The greatest number of differentially expressed genes occurred at 8 months of age, in the spring a full year before the obvious physiological transformation from stream‐dwelling parr to sea water‐adaptable smolts begins for migrant individuals. Sex and age exhibited considerable effects on differential gene expression between migrants and resident offspring. Differential gene expression was observed in genes previously associated with migration, but also in genes previously unassociated with early life history divergence. Pathway analysis revealed coordinated differential expression in genes related to phototransduction, which could modulate photoperiod responsiveness and variation in circadian rhythms. The role for early differentiation in light sensitivity and biological rhythms is particularly intriguing in understanding early brain processes involved in differentiation of migratory and resident life history types.

Matrix detachment and proteasomal inhibitors diminish Sulf-2 expression in breast cancer cell lines and mouse xenografts - Ashwani Khurana; Deok Jung-Beom; Xiaoping He; Sung-Hoon Kim; Robert C. Busby; Laura Lorenzon; Massimo Villa; Alfonso Baldi; Julian Molina; Matthew P. Goetz; Viji Shridhar (Clinical & Experimental Metastasis, 2013)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)